MOMETAZON FUROAT FOR ATOPIC DERMATITIS IN CHILDREN - T.S. Shaipov; L.P. Mazitova (Union of pediatricians of Russia, 2007)
Atopic dermatitis is one of the most prevalent reasons for skin lesions in the infancy. The medications of the first line therapy for this disease are topic glucocorticosteroids (TGCS). The survey has analyzed the efficiency of a new TGCS - mometazon furoat - for treating atopic dermatitis of children. The action mechanism of this medication is connected with the suppression of proinflammatory cytokinins synthesis (Il6, Il1, TNF). Mometazon furoat has clear anti inflammatory, antipruritic and anti exudative action. The treatment results proved high efficiency of the medication both for noncomplicated atopic dermatitis and for atopic dermatitis complicated with a secondary infection.Key words: atopic dermatitis, topic glucocorticosteroids, therapy, children.